Implementasi e-Faktur Versi 4.0 pada Distributor Makanan Ringan di Pontianak - Yodianto, Alex; Yantiana, Nella; Heniwati, Elok (Journal of Innovation in Management, Accounting and Business, 2024)
The e-Faktur application has emerged as the principal instrument for meeting tax requirements for commercial entities in Indonesia, particularly for Taxable Entrepreneurs (PKP). This study seeks to examine the execution of e-Faktur version 4.0, emphasizing its effects and the obstacles encountered during its application at a snack food distributor in Pontianak, employing a descriptive qualitative approach. Data were gathered via interviews and observations. This study's findings reveal that the primary limitation is the validation of the Population Identification Number (NIK). A trustworthy information system is required for PKP to directly authenticate NIK, hence preventing administrative sanctions in cases of non-validation.